Investigation on a Bio-Composite Material as Acoustic Absorber and Thermal Insulation - Domenico Curto; Andrea Guercio; Vincenzo Franzitta (Energies, 2020)
In order to limit the anthropic emissions of CO2, research is currently investigating new materials for the building sector. The main purpose is the reduction in the embodied energy consumption, especially in the residential sector, and consequently the limitation of the direct and indirect utilization of fossil fuels, for the indoor heating, cooling, and ventilation services. Indeed, the residential sector is affected by a high energy demand, thus the choice of improved materials is fundamental to improve the sustainability. All phases: construction, building life, and dismantling are impacting in terms of resource and energy consumption, both associated with the emissions of pollutants in the atmosphere. The aim of this experimental research is to study the thermal insulation and the acoustic absorption of a material composed by natural lime, water, and shives from sativa hemp, a variety of hemp usable for industrial applications. In order to assess the main characteristics of this material, some specimens have been made according to required shapes and sizes to test them in specific machines. The results obtained from the tests are compared with the values of similar lime-based materials already available on the market. The comparison shows how, in certain aspects, the lime and hemp shives materials represent a concrete alternative to conventional materials. This completely natural material would like to achieve thermal and acoustic comfort in indoor environments.